Optimal fiscal policy over the business cycle - Filippo Occhino (Rutgers University, Department of Economics, 2005)
How should taxes, government expenditures, the primary and fiscal surpluses and government liabilities be set over the business cycle? We assume that the government chooses expenditures and taxes to maximize the utility of a representative household, utility is increasing in government expenditures, only distortionary labor income taxes are available, and the cycle is driven by exogenous technology shocks. We first consider the commitment case, and characterize the Ramsey equilibrium. In the case that the utility function is constant elasticity of substitution between private and public con- sumption and separable between the composite consumption good and leisure, taxes, government expenditures and the primary surplus should all be constant positive frac- tions of production, and both government liabilities and the fiscal surplus should be positively correlated with production. Then, we relax the commitment assumption, and we show how to determine numerically whether the Ramsey equilibrium can be sustained by the threat to revert to a Markov perfect equilibrium. We find that, for realistic values of the preferences discount factor, the Ramsey equilibrium is sustain- able. Keywords: Fiscal policy, Commitment, Time-consistency, Ramsey equilibrium, Markov perfect equilibria, Sustainable equilibria.
Keywords: E62; 330; Fiscal policy; Commitment; Time-consistency; Ramsey equilibrium; Markov perfect equilibria; Sustainable equilibria; Finanzpolitik; Öffentliche Ausgaben; Konjunktur; Einkommensteuer; Optimale Besteuerung; Theorie